Financial reporting in Ireland - Moretti, Delphine (OECD Publishing, 2019)
The OECD Review of Financial Reporting in Ireland assesses opportunities and challenges associated with adopting accruals in Ireland for government accounting. Due to issues with the comprehensiveness and legibility of the current financial reports, the Review recommends that going forward, the Irish Government establish accrual financial statements compliant with international standards for its departments and offices and harmonise accounting standards used by entities within the general government sector. The report notes that accrual data would be a "building block" for richer, more reliable fiscal information, which would, in turn, help formulate improved assumptions for fiscal forecasts and be better equipped to identify fiscal risks. Beyond the adoption of accrual accounting, this report proposes that the Irish Government considers modernising its financial reporting framework by preparing integrated reports for departments and offices and consolidated financial statements. Integrated accounts for departments and offices would provide an overview of each department's resources and spending alongside information on their strategy and performance. This would enhance and improve scrutiny and examination of departmental performance by the Committee of Public Accounts and by the Oireachtas Sectoral Committees
Keywords: Governance; Ireland